The impact of the enhanced recovery pathway and other factors on outcomes and costs following hip and knee replacement: routine data study - Andrew Judge; Andrew Carr; Andrew Price; Cesar Garriga; Cyrus Cooper; Daniel Prieto-Alhambra; Fraser Old; George Peat; Jacqueline Murphy; Jose Leal; Karen Barker; Lydia Underdown; et al. (Health Services and Delivery Research, 2020)
Background: There is limited evidence concerning the effectiveness of enhanced recovery programmes in hip and knee replacement surgery, particularly when applied nationwide across a health-care system. Objectives: To determine the effect of hospital organisation, surgical factors and the enhanced recovery after surgery pathway on patient outcomes and NHS costs of hip and knee replacement. Design: (1) Statistical analysis of national linked data to explore geographical variations in patient outcomes of surgery. (2) A natural experimental study to determine clinical effectiveness of enhanced recovery after surgery. (3) A qualitative study to identify barriers to, and facilitators of, change. (4) Health economics analysis to establish NHS costs and cost-effectiveness. Setting: Data from the National Joint Registry, linked to English Hospital Episode Statistics and patient-reported outcome measures in both the geographical variation and natural experiment studies, together with the economic evaluation. The ethnographic study took place in four hospitals in a region of England. Participants: Qualitative study – 38 health professionals working in hip and knee replacement services in secondary care and 37 patients receiving hip or knee replacement. Interventions: Natural experiment – implementation of enhanced recovery after surgery at each hospital between 2009 and 2011. Enhanced recovery after surgery is a complex intervention focusing on several areas of patients’ care pathways through surgery: preoperatively (patient is in best possible condition for surgery), perioperatively (patient has best possible management during and after operation) and postoperatively (patient experiences best rehabilitation). Main outcome measures: Patient-reported pain and function (Oxford Hip Score/Oxford Knee Score); 6-month complications; length of stay; bed-day costs; and revision surgery within 5 years. Results: Geographical study – there are potentially unwarranted variations in patient outcomes of hip and knee replacement surgery. This variation cannot be explained by differences in patients, case mix, surgical or hospital organisational factors. Qualitative – successful implementation depends on empowering patients to work towards their recovery, providing post-discharge support and promoting successful multidisciplinary team working. Care processes were negotiated between patients and health-care professionals. ‘Good care’ remains an aspiration, particularly in the post-discharge period. Natural experiment – length of stay has declined substantially, pain and function have improved, revision rates are in decline and complication rates remain stable. The introduction of a national enhanced recovery after surgery programme maintained improvement, but did not alter the rate of change already under way. Health economics – costs are high in the year of joint replacement and remain higher in the subsequent year after surgery. There is a strong economic incentive to identify ways of reducing revisions and complications following joint replacement. Published cost-effectiveness evidence supports enhanced recovery pathways as a whole. Limitations: Short duration of follow-up data prior to enhanced recovery after surgery implementation and missing data, particularly for hospital organisation factors. Conclusion: No evidence was found to show that enhanced recovery after surgery had a substantial impact on longer-term downwards trends in costs and length of stay. Trends of improving outcomes were seen across all age groups, in those with and without comorbidity, and had begun prior to the formal enhanced recovery after surgery roll-out. Reductions in length of stay have been achieved without adversely affecting patient outcomes, yet, substantial variation remains in outcomes between hospital trusts. Future work: There is still work to be done to reduce and understand unwarranted variations in outcome between individual hospitals. Study registration: This study is registered as PROSPERO CRD42017059473. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 4. See the NIHR Journals Library website for further project information.